The relationship between height velocity and growth hormone secretion in short prepubertal children. - Hindmarsh, P; Smith, P; Brook, C; Matthews, DR (1987)
We have performed 24 h growth hormone (GH) profiles in 50 short prepubertal children aged between 5.2 and 12.9 years, growing with height velocity standard deviation scores (SDS) between 0.4 and -3.9. There was an asymptotic relationship between height velocity and spontaneous GH secretion described by the equation: height velocity SDS = A-B(e-cx), where A, B and C are constants and x is a measure of spontaneous GH secretion. We considered GH pulse amplitude to be the better description of spontaneous GH secretion as duration of the GH pulse (the time component of area under the curve) contributed little to the relationship between height velocity and area under the pulse. The distribution of GH secretion was continuous and there was no dividing point between GH insufficiency and sufficiency. Similar overlap was observed when the results of GH responses to insulin induced hypoglycaemia were considered; 14% of slowly growing children (height velocity SDS less than -0.8), had a response greater than 15 mU/l. Likewise serum IGF-I concentrations could not clearly separate slowly growing children from normal individuals. We conclude that height velocity, which ultimately determines height achieved, is controlled predominantly by GH pulse amplitude. The findings suggest that short normal children growing along or parallel to the third height centile could be made to grow faster by the administration of exogenous GH.